Inhibition of CK2α down-regulates Hedgehog/Gli signaling leading to a reduction of a stem-like side population in human lung cancer cells. - Shulin Zhang (Public Library of Science (PLoS), 2012)
Protein kinase CK2 is frequently elevated in a variety of human cancers. The Hedgehog (Hh) signaling pathway has been implicated in stem cell maintenance, and its aberrant activation has been indicated in several types of cancer, including lung cancer. In this study, we show that CK2 is positively involved in Hh/Gli signaling in lung cancer cell lines A549 and H1299. First, we found a correlation between CK2α and Gli1 mRNA levels in 100 primary lung cancer tissues. Down-regulation of Gli1 expression and transcriptional activity were demonstrated after the silencing of CK2α in lung cancer cells. In addition, CK2α siRNA down-regulated the expression of Hh target genes. Furthermore, two small-molecule CK2α inhibitors led to a dose-dependent inhibition of Gli1 expression and transcriptional activity in lung cancer cells. Reversely, forced over-expression of CK2α resulted in an increase both in Gli1 expression and transcriptional activity in A549 cells. Finally, the inhibition of Hh/Gli by CK2α siRNA led to a reduction of a cancer stem cell-like side population that shows higher ABCG2 expression level. Thus, we report that the inhibition of CK2α down-regulates Hh/Gli signaling and subsequently reduces stem-like side population in human lung cancer cells.